Chatter avoidance for high performance machining - Esterling, Donald; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2003)
The presenter talk about the chatter avoidance for high performance machining in high speed machining in order to maintain the goodness in this industry
Code no : DV03PUB77
Recorded at the High Speed Machining Technical Conference, Apr. 8 & 9, 2003, Itasca, Ill.
Title from title screen
Presenter: Donald Esterling
Keywords: High-speed machining; Machining; Manufacturing processes